2018
DOI: 10.1007/s00702-018-1843-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between gait variability and cognitive functions differs between fallers and non-fallers in MS

Abstract: The objective of the study was to determine if cognitive function is associated with step time variability in people with multiple sclerosis (PwMS). The study included 355 PwMS (218 women), average age 41.1 (SD = 13.5), disease duration 5.9 (SD = 7.3) years, and a median expanded disability status scale score of 2.5. We separately analyzed the sample group of fallers and non-fallers based on their fall history. Gait variability was measured by an electronic walkway and all participants completed a computerized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…17 Furthermore, step time variability was linked to global cognition (based on a computerized cognitive test battery) in people with multiple sclerosis without a fall history (n = 200). 16 Worth noting, the mean Expanded Disability Status Scale score of the people with multiple sclerosis nonfallers was 2.1, which is relatively close to the Expanded Disability Status Scale score of the present adolescents with multiple sclerosis (mean score = 1.6). Accordingly, we speculate that the relationship between gait variability and information-processing speed occurs at the very early phases of the multiple sclerosis disease, prior to the development of significant mobility difficulties.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…17 Furthermore, step time variability was linked to global cognition (based on a computerized cognitive test battery) in people with multiple sclerosis without a fall history (n = 200). 16 Worth noting, the mean Expanded Disability Status Scale score of the people with multiple sclerosis nonfallers was 2.1, which is relatively close to the Expanded Disability Status Scale score of the present adolescents with multiple sclerosis (mean score = 1.6). Accordingly, we speculate that the relationship between gait variability and information-processing speed occurs at the very early phases of the multiple sclerosis disease, prior to the development of significant mobility difficulties.…”
Section: Discussionsupporting
confidence: 63%
“…This tool is detailed in our previous paper. 16 Briefly, outcome measurements included the following cognitive domains: verbal and nonverbal memory, executive function, visual spatial processing, verbal function, attention, information processing speed, and motor skills. Each outcome parameter was normalized and fit an IQ-like scale (mean 100, SD 15) in an age- and education-specific fashion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little has been reported on how specific cognitive domains interact with aspects of movement in dual task behaviors, particularly for individuals with ND. However, in a recent study exploring associations between several cognitive domains and gait variability in people with MS, Kalron et al (2018) found that global cognition, executive function subcategory, and cognitive motor skills were associated with step time variability in non-fallers with MS, but no associations for the fallers. Exploring similar associations in people with PD, Stegemöller et al (2014) found that cognitive processing speed correlated with stride length and walking speed, and executive function correlated with step width variability.…”
Section: Clinical Considerations Of Dual Task Performance In Ndmentioning
confidence: 93%
“…Postural sway captures the horizontal acceleration of the person's center in all directions, most often in the mediolateral and anterior-posterior planes. Typically, sway area, sway range, sway velocity, and jerk, defined as the smoothness of the trunk sway (rate of change), are extracted and Gait cycle / stride duration s, ms Blin et al, 1990;Ginis et al, 2017;Shah et al, 2020Benedetti et al, 1999Straudi et al, 2013;Müller et al, 2021 Cadence steps/min Curtze et al, 2015;Horak et al, 2016;Iijima et al, 2017Martin et al, 2006Straudi et al, 2013;Leone et al, 2018 Gait velocity / speed m/s, cm/s Herman et al, 2014;Galna et al, 2015;Mancini, 2020 Benedetti et al, 1999;Remelius et al, 2012;Müller et al, 2021 Stride / step length m Rochester et al, 2014;Ferrari et al, 2016;Cebi et al, 2020Martin et al, 2006Remelius et al, 2012;Leone et al, 2018 Double support time % cycle, % stride Blin et al, 1990;Curtze et al, 2015;Shah et al, 2020Benedetti et al, 1999Straudi et al, 2013;Leone et al, 2018 Stride / step time variability s Herman et al, 2014;Galna et al, 2015;Ma et al, 2020aMoon et al, 2015Allali et al, 2016;Kalron et al, 2018 Knee (lower leg) ROM degree Dewey et al, 2014;Curtze et al, 201...…”
Section: Balance Measuresmentioning
confidence: 99%